A multi-angle analysis of injury induced by supplementation of soybean meal in Litopenaeus vannamei diets - Peng, Kai; Qiu, Jianqiang; Li, Chaozheng; Lu, Huijie; Liu, Zhenxing; Liu, Ding; Huang, Wen (Frontiers in Microbiomes, 2023)
Soybean meal is considered as one of the major components in Litopenaeus vannamei diets. However, most previous studies have focused on evaluating the effects of soybean meal on L. vannamei from the perspective of growth, physiological and feed utilization, information regarding analysis of serum metabolites, antioxidant and immune response and intestinal microbiota is limited. Five diets were prepared by including 20% (T20), 28% (T28), 35% (T35), 42% (T42) and 50% (T50) of soybean meal. A total of 600 shrimp were randomly distributed into 20 tanks (30 shrimp per tank) with 4 tanks being assigned to each diet. Shrimp were fed to apparent satiation during the 42-d feeding trial. Results showed that serum globulin, alanine aminotransferase and aspartate aminotransferase were linearly increased (P < 0.01), but high density lipoprotein cholesterol was linearly decreased (P < 0.001) as dietary soybean meal increasing. Supplementation of soybean meal in shrimp diets linearly and quadratically increased (P < 0.05) serum total antioxidant capacity, catalase, malondialdehyde, nitric oxide synthase and phenoloxidase. Hepatocytes in T35, T42 and T50 were shown to have different degrees of vacuolar degeneration, hepatic corpuscle atrophy and starlike lumen lose. Dietary inclusion of soybean meal altered the composition of intestinal bacterial microbiota at phylum level especially increased the abundance of potentially pathogenic bacteria, whereas it had minimal impact on bacterial genera and had no significant influence on the bacterial diversity. This study suggests that dietary supplementation of soybean meal in L. vannamei diets exceed 28% induced inflammation and oxidant damage of hepatopancreas and increased the risk of intestinal disease.